Dobra komplementarne w modelu Debreu - Lipieta, Agnieszka (Complementary commodities in Debreu economy, 2007)
We assume that at least two commodities in a Debreu model are complementary. It means that all the individual consumption sets are contained in a proper subspace V of (V c 911). Let the individual production sets are also the subsets of V and let p e is an equilibrium price vector. We show that there exists such a vector p t- c V that replacing prices p by p v will not destroy the equilibrium. As a result the whole model becomes less complicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 102-112